Pseudotyped recombinant adeno-associated viral vectors mediate efficient gene transfer into primary human CD34+ peripheral blood progenitor cells - Veldwijk, Marlon Romano; Sellner, Leopold; Stiefelhagen, Marius; Kleinschmidt, Jürgen; Maier-Laufs, Stephanie; Topaly, Julian; Frühauf, Stefan; Zeller, W. Jens; Wenz, Frederik (Cytotherapy, 2010)
Because of their pluripotency, human CD34+ peripheral blood progenitor cells (PBPC) are targets of interest for the treatment of many acquired and inherited disorders using gene therapeutic approaches. Unfortunately, most current vector systems lack either sufficient transduction efficiency or an appropriate safety profile. Standard single-stranded recombinant adeno-associated virus 2 (AAV2)-based vectors offer an advantageous safety profile, yet lack the required efficiency in human PBPC.